A critical role of thrombin/PAR‐1 in ADP‐induced platelet secretion and the second wave of aggregation. Issue 5 (15th May 2013) - Jiang, L.; Xu, C.; Yu, S.; Liu, P.; Luo, D.; Zhou, Q.; Gao, C.; Hu, H.
Summary Background The stable or second wave of platelet aggregation often observed in ADP‐stimulated platelet‐rich plasma (PRP) with an artificially lowered extracellular calcium level has been attributed to enhanced thromboxane A2 (TXA2) generation and inhibition of ectonucleotidase activity. However, the role of thrombin in ADP‐induced platelet secretion and the second wave of aggregation is unknown. Objectives and Methods We employed aggregometry, flow cytometry, immunoblotting and ELISA to determine whether and how thrombin participates in ADP‐induced platelet secretion and the second wave of aggregation. Results ADP induces a phosphoinositide 3‐kinase (PI3K) pathway‐dependent thrombin generation, presumably resulting from the cleavage of αIIbβ3‐associated prothrombin. Generated thrombin subsequently activates protease‐activated receptor‐1 (PAR‐1) and mediates dense granule secretion and the second wave of platelet aggregation in ADP‐stimulated citrated PRP. Thus, ADP‐induced dense granule secretion and the second wave of platelet aggregation in PRP were similarly and non‐additively blocked by thrombin inhibitor hirudin, PAR‐1 antagonist SCH‐79797 or PI3K inhibitor wortmannin. Moreover, ADP stimulation caused the dissociation of prothrombin from αIIbβ3 and an increased plasma thrombin level; both were prevented by wortmannin. Furthermore, the wortmannin‐inhibited second wave of platelet aggregation by ADP was restored by a subaggregation concentration of PAR‐1 activating peptide SFLLRN. Blocking TXA2 production with indomethacin or restoring extracellular calcium to physiological concentration did not influence this thrombin/PAR‐1 dependence. Conclusions A PI3K‐dependent thrombin generation and the resultant PAR‐1 activation serve as an indispensable mechanism to relay the platelet activation process induced by ADP.